Korean dose coefficients for external exposures from air contamination - Bangho Shin; Chansoo Choi; Yumi Lee; Ji Won Choi; Yeon Soo Yeom (Nuclear Engineering and Technology)
In the present study, the Korean-specific dose coefficients (DCs) for air contamination were produced using the adult mesh-type reference Korean phantoms (MRKPs). The DCs were calculated using the Geant4 radiation transport code, employing the same calculation methods and phase-space source data used to calculate the DCs in ICRP Publication 144. We investigated the dosimetric impacts of the Korean-specific DCs against the ICRP144 values. For organ doses, the photon DCs showed good agreement at energies ≥0.5 MeV, with differences generally less than 30 %. At energies <0.5 MeV, on the other hand, significant differences of up to 44 times were observed at 0.02 MeV for female urinary bladder. For electrons, more pronounced differences were observed not only at energies <0.5 MeV (differences of up to 859 times at 0.015 MeV for male testes) but also at energies ≥0.5 MeV (differences of up to 12 times at 0.5 MeV for male testes). For effective doses, the photon DCs were in good agreement (differences <15 %), whereas the electron DCs showed significant differences of up to 9.2 times. The produced Korean-specific DCs will be valuable for dose estimates in air contamination exposures, providing reliable doses specific to the Korean populations.